Analysis of the Impact of Intellectual Capital and Good Corporate Governance on Financial Distress in the Healthcare Sector of the Indonesia Stock Exchange - Rita Ninda Sari; Fitrini Mansur; Dica Lady Silvera (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to identify the effect of intellectual capital and good corporate governance on financial distress. The independent variables used are intellectual capital and good corporate governance which is proxied by institutional ownership, board of directors, independent commissioners, and audit committee. The dependent variable in this study is financial distress. This study uses a quantitative approach. This research focuses on the population contained in the healthcare sector companies listed on the Indonesia Stock Exchange in 2021-2023. This study uses purposive sampling method for sample selection with a total sample of 23 companies. Data analysis in this study was carried out using multiple linear regression techniques, which were operated with the IBM SPSS program version 26. The findings of this study show that partially intellectual capital, institutional ownership, and audit committee have an effect on financial distress. Partially independent commissioners and the board of directors have no effect on financial distress. Simultaneously intellectual capital, institutional ownership, board of directors, independent commissioners, and audit committee affect financial distress